The coins of Herod: a modern analysis and Die Classification - Ariel, Donald T. (Ancient Judaism and early Christianity, 2012)
Introduction -- Gold and silver coins during Herod's reign -- A typology of Herod's coins -- The dies and minting technology -- The location of the mint or mints -- The iconography -- The inscriptions -- Herod's coins in hoards -- Herod coins in archaeological contexts -- Geographical distribution of Herod's coins -- A relative chronology of Herod's coins --Towards an absolute chronology of Herod's coins